ANALYSIS OF RASPBERRY PI BASED ATM THEFT MONITORING AND SECURITY SYSTEM - rani, G.Jhansi; kumari, D.Raghava; Anitha, M.; Sarita, B. (International Journal of Psychosocial Rehabilitation, 2020)
This project is designed to prevent theft of ATM from robberies to overcome our society’s inconvenience in existing technology. Safety experts are ready to assist people in the process of enhancing ATM safety and ATM loss reduction systems with ATM video surveillance camera and ATM monitoring options. In order to avoid such a situation, the project will produce real time sensor information, images of theft and door and shutter load mechanism, and collect money, as the tart running police will not catch robbery. The system is implemented on the Raspberry Pi credit card size board used for image processing. Security mechanism is provided by the consecutive actions such as when the ATM user swipe the card , person’s captured image and SMS of alert is sent to the ATM card holder using the raspberry pi processor and GSM module and depending upon the card holders decision, either the access will be given to the user or the access will be denied and depending upon the entered amount by the user through keypad and the money dispense unit will work thereby providing advance security during the withdrawal of the money from the ATM.